Pengaruh Model Pembelajaran SAVI Berbantuan Media Triorama Ekosistem Terhadap Hasil Belajar Ilmu Pengetahuan Alam - Kreswinnanda, Divya; Suryawan, Ari; Mardiana, Tria (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2022)
This study aims to determine the effect of the SAVI learning model assisted by the Ecosystem Triorama media on the learning outcomes of natural science students of class VI SDIT Al-Ma'ruf Tegalrejo. The type of research used in this research is Pre Experimental with the One Group Pretest Posttest Design model. The subjects in this study were class VI SDIT Al- Ma'ruf Tegalrejo totaling 20. The data collection method used a pretest which was carried out before the treatment was given and the posttest was carried out after being given treatment in the form of multiple choice questions. The sampling technique used was saturated sampling (exhausting sampling). Collecting data through pretest-posttest questions and then analyzed using the Paired Sample test. The results showed that the SAVI model assisted by the Ecosystem Triorama media had an effect on learning outcomes in Natural Sciences. This is evidenced by the results of the Paired Sample test analysis in the experimental class with a probability value of sig. (2-tailed) 0.000 (0.000<0.05). Based on the analysis and discussion, there is a difference in the average pretest and posttest scores, namely the pretest 62.5 and the posttest 77.5, both of which have a difference of 15.00. The results of the study can be concluded that the use of the SAVI model assisted by the Ecosystem Triorama media has an effect on learning outcomes in Natural Sciences.